Pengaruh Investasi dan Penanaman Modal Dalam Negeri (PMDN) Meningkatkan Pertumbuhan Ekonomi Upaya Mewujudkan Rethinking Goverment - Aprilia, Nikmatul Riskiyah; Arifin, Deswita Aurellia; Djasuli, Mohammad (Jurnal Ilmiah Wahana Pendidikan, 2024)
The condition of the Covid-19 pandemic has had a negative impact on the economy in all countries, including Indonesia. Indonesia's economic growth is weakening. Large-Scale Social Restrictions (PSBB) make the economy decline in formal and non-formal sectors. The decline in consumption levels as an indicator of economic growth contributed to the sluggish economy. However, investment, which is also an indicator of gross domestic product, has not shown a decline and has even increased from year to year. The government's role in this matter is critical. During the pandemic, the government tried to maintain investment to not worsen economic conditions through various policies. After the pandemic, the government encouraged investment both domestic and foreign to realize development in Indonesia.